The Project Stock-taking of Monuments in Rotterdam (Bulletin KNOB, 1990)
Within the framework of the Project Stock-taking of Monuments (MIP), 1850-1940 research has been executed in Rotterdam. The researchers started with a study on the general development of the town comprising her geography, the historical town, infrastructure, trade and shipping, industrial development, sector of services, culture, town-planning and architectural development.The transformation of Rotterdam's harbour into a transit harbour of world stature as well as urban extensions brought about expansive spatial development during the period 1850-1940. The first planned extension to the west of the old town was executed after a design of town-architect W. N. Rose in 1850. The quarters Cool and Rubroek (1858) and the Waterproject, a moat structure which has been laid out around the old town (1854) are designed by the same architect.More influential than the plan of extension by town-architect G. J. de Jongh (1883) was the Building Regulation of 1857 determining street corners to be splayed for the sake of traffic. Promoted by the lay-out of the channel the Nieuwe Waterweg (1872), the introduction of railways and the increase of shipping at the end of the 19th century one concentrated especially on the extension of the harbour. Many industries like the petrochemical settled down in this area. House construction on the southern part was only realized on remaining areas after the lay-out of harbours, industrial sites and railways.After the turn of the century the notion of the garden-city influenced the layout of the villages Heyplaat, Vreewijk and Bloemhof. Besides in 1901 the Act of Housing permitted subsidized house construction and consequently experiments with new building methods, which during the twenties and thirties resulted in the soberly decorated building blocks of a.o. the quarters Oud Mathenesse and Spangen and the concrete villages Kossel and Stuhlemeyer.At the end of the 19th century the municipality supplied the increasing population with provisions like waterworks, sewerage, gas and electricity. Provisions on the field of sanitary measures, sports and relaxation came into being. Renewal of transport by the introduction of motorbus, tram and automobile demanded adaptation of the narrow urban structure. Almost all of these operations from the period 1850-1940 in the centre of Rotterdam have been destroyed during the war.The first reconnaissance by the researchers resulted in a partition of the town into eighteen districts. Stocktaking of valuable objects and areas happened according to provisional general descriptions, which resulted in a truce from farms and offices to tram shelters and bridges. Representativity of socio-historical developments was starting point at the selection.At several categories the quality of architectural design has been included. Town-planning criteria like the quality of spatial draft, historical signification or signification in the larger environment are used to select areas of special value. The criteria 'wholeness' or 'scarceness' of the above-mentioned qualities often were hard to apply by the drastic changes several areas underwent by urban renewal. Thus the recent Project Stock-taking of Monuments provides insight into Rotterdam's spatial development during the period 1850-1940.Buildings and structures have been described against a background of geographical and historical development. Most of these monuments cannot be considered for a qualification as municipal or governmental monument. Different from the traditional protection of monuments in Rotterdam an integrated policy of monuments has to be developed. Here protection concerns larger ensembles. In cooperation with designers will have to be investigated how earlier architecture and townplanning can be worked up in extant and future design-practices.